Call admission control for a wireless mobile multimedia network serving narrowband and wideband customers - Mohamed, Nagla Osman; Deniz, Derviş Z. (My University, 2006)
Call admission control (CAC) strategies for multimedia traffic in wireless mobile networks are considered. Particularly, a wireless cell serving two types of customers; narrowband (n-type) which require 1 channel and wideband (w-type) which require bw?1 channels is studied. New and handoff calls of both types are modeled. System performance is obtained by solving the resulting stochastic matrices using matrix algorithmic techniques. The technique developed provides exact results in a fast and efficient manner. The results show significant QoS improvement for handoff calls in comparison with that of a complete sharing system. © IEEE.
International Conference on Digital Telecommunications 2006, ICDT'06 --
Keywords: Algorithms; Congestion control (communication); Data structures; Matrix algebra; Multimedia systems; Quality of service; Matrix algorithmic techniques; Multimedia traffic; Wireless mobile multimedia networks; Wireless networks